Comparison of transfer shock and graduation rates across engineering transfer student populations. Issue 1 (20th October 2021) - Smith, Natasha L.; Grohs, Jacob R.; Van Aken, Eileen M.
Abstract: Background: Increasing the persistence of engineering transfer students can help meet the US national priority of increasing the number of engineering graduates. Many transfer students experience a decrease in their grade point average (GPA) at their receiving institution, known as transfer shock, which can lead to them leaving the institution. This GPA decrease is found to be more prevalent in engineering transfer students. Purpose/Hypothesis: The purpose of this study is to analyze a single institutional dataset to determine when transfer shock occurs, how it differs among engineering transfer student subgroups, and if transfer shock is a predictor of graduation within 4 years in engineering. Design/Method: A 10‐year dataset with 789 engineering transfer students was used in this study, and the engineering transfer students were split into four subgroups. Multiple statistical analyses were conducted, including Welch's F ‐test, chi‐square, and logistic regression, to understand differences in transfer shock during the first three terms of enrollment as well as 4‐year graduation rates among each subgroup. Results: Transfer shock extends through the first three post‐transfer terms, resulting in transfer norming. The engineering transfer student subgroups experience different levels of transfer norming; however, the subgroups were not predictors of graduation. The predictors were the transfer GPA and the transfer norming in the first three post‐transfer terms of enrollment. Conclusions: Engineering transfer students are not a homogeneous population; there are key differences between lateral and vertical transfer students. More strategic, longitudinal programming and decision‐making should be considered by institutions.